2018
DOI: 10.1002/ejlt.201800262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Extraction Technique and Genotype on the Oil Yield and Composition of Lipophilic Compounds in the Oil Recovered from Japanese Quince (Chaenomeles japonica) Seeds

Abstract: The impact of the extraction technique and genotype on the oil yield and profile/concentration of fatty acids, tocopherols, sterols, and squalene in oil obtained from the seeds of three Japanese quince (Chaenomeles japonica) cultivars (“Rondo,” “Darius,” and “Rasa”) are studied. The oil recovery from Japanese quince seeds is affected by two factors; extraction technique, and genotype. The lowest oil recovery is recorded for the cold‐press method and cv. “Rondo,” and the highest for ultrasonic extractions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…The similar fatty acid composition is found in the quince seed oil obtained by Soxhlet extraction ( Table ). Other research results showed that the extraction method did not impact fatty acid and tocopherol composition in quince seed oil, but genotype has a statistically significant impact …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The similar fatty acid composition is found in the quince seed oil obtained by Soxhlet extraction ( Table ). Other research results showed that the extraction method did not impact fatty acid and tocopherol composition in quince seed oil, but genotype has a statistically significant impact …”
Section: Resultsmentioning
confidence: 91%
“…The yield of quince seed oil, which was obtained by Soxhlet method, ranges from 6.1 % to 10.1 %, and from 10 % to 20 %, when finely ground seeds undergo extraction with refluxing petroleum ether . Subsequent studies have shown that quince seed oil yield depends on the extraction method . The apples and pears belong to the same Rosaceae family as the quince Chaenomeles japonica .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mohammadpour et al [32] reported that UAE increased the Moringa peregrina seed oil yield (53.101%) compared with the Soxhlet extraction (SXE) (43%), while the extraction time was much shorter (26.3 min vs. 11 h). Górnaś et al [33] showed the result that SXE, SFE and cold-pressing extraction (CPE) assays were less efficient in comparison with UAE on average by 3%, 21%, and 27% for seed oil recovery from Japanese quince (Chaenomeles japonica), respectively. In this study, the extraction yields of S. delavayi and S. mukorossi kernel oils could reach 43.67% and 45.96% under the optimized UAE conditions, respectively.…”
Section: Effect Of Process Parameters and Process Optimizationmentioning
confidence: 99%